Macroeconomic Effects of Trade Tariffs: A Case Study of the U.S.-China Trade War Effects on the Economy of the United States - Žemaitytė, Sandra; Urbšienė, Laimutė (Organizations and Markets in Emerging Economies, 2020)
This paper explores the macroeconomic effects of trade tariffs in the context of the recent trade conflict between the United States and China. The focus is laid on two trade war scenarios, and one of them takes into account the effects of the COVID-19 pandemic on the global trade flows. After deploying the partial equilibrium SMART model, the authors conclude that solely due to the trade war with China, in 2020, the US total trade balance will improve by 41,020 million USD (0.21% of real GDP), while 43,777 million USD (0.22% of real GDP) of the US imports will have to be sourced from other countries. The US trade intensity with China and welfare will decline. However, our study has found that the potential economic consequences of COVID-19 will reduce the relative effects of the trade war. The study has revealed that the United States economy will benefit from the trade war, which can be explained by a relatively weak China’s retaliatory response. Nevertheless, the US agriculture and automotive sectors will suffer most.
Keywords: Trade tarrifs; US-China trade war; trade balance; welfare